2016
DOI: 10.1007/s12250-015-3693-1
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA expression profile of Coxsackievirus A16 infected RD cells identified by RNA-seq

Abstract: Coxsackievirus A16 (CVA16) is one of major pathogens of hand, foot and mouth disease (HFMD) in children. Long non-coding RNAs (IncRNAs) have been implicated in various biological processes, but they have not been associated with CVA16 infection. In this study, we comprehensively characterized the landscape of IncRNAs of normal and CVA16 infected rhabdomyosarcoma (RD) cells using RNA-Seq to investigate the functional relevance of IncRNAs. We showed that a total of 760 IncRNAs were upregulated and 1210 IncRNAs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The genes transcribed within a 100 kb window upstream or downstream of lncRNAs were considered as potential cis target genes [79]. The second algorithm was used to identify potential trans targets based on RNA sequence complementarity (mRNA-lncRNA) and RNA duplex energy prediction [80,81]. Based on the RNA duplex energy (Free energy < − 50) assessed by RIsearch algorithms [82], the differentially expressed genes and lncRNAs were considered as potentially involved in trans-interaction.…”
Section: Target Gene Prediction and Functional Analysis Of Lncrnasmentioning
confidence: 99%
“…The genes transcribed within a 100 kb window upstream or downstream of lncRNAs were considered as potential cis target genes [79]. The second algorithm was used to identify potential trans targets based on RNA sequence complementarity (mRNA-lncRNA) and RNA duplex energy prediction [80,81]. Based on the RNA duplex energy (Free energy < − 50) assessed by RIsearch algorithms [82], the differentially expressed genes and lncRNAs were considered as potentially involved in trans-interaction.…”
Section: Target Gene Prediction and Functional Analysis Of Lncrnasmentioning
confidence: 99%
“…Previously, we focused on the molecular epidemiology and pathogenic mechanism of CA16 and found that CA16 infection induces apoptosis (Zhu et al, 2013) and regulates long noncoding RNA (lncRNA) (Shi et al, 2016), which regulates viral replication (Zhu et al, 2013;Shi et al, 2016). In this study, we found that granulophagy occurred during CA16 infection and facilitated viral replication, and CA16-induced granulophagy also repressed the antiviral response.…”
Section: Introductionmentioning
confidence: 85%
“…The cells were maintained at 37°C and 5% CO 2 . CA16 is a laboratory strain that has been completely sequenced and belongs to the B1 genotype (Shi et al, 2015(Shi et al, , 2016. Plasmids expressing the His-tagged fulllength MAVS and deletion mutants lacking either the CARD-like domain (∆CARD) or the transmembrane domain (∆TM) were amplified by PCR and cloned into the pcDNA 6/V5-His B vector (Thermo Fisher Scientific, USA).…”
Section: Methodsmentioning
confidence: 99%